The Directive on Adequate Minimum Wages in the European Union and Its Potential Impact on National Law - Mądrzycki, Błażej; Pisarczyk, Łukasz (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The objective of this paper is to analyse the mechanisms established by the Directive 2022/2041 for the purpose of determining adequate and fair minimum wages and promoting collective bargaining. The authors present the objectives, scope of application, and legal nature of the provisions of the Directive, and subsequently undertake the clarification of the doubts that have emerged in the preparatory stages of the process of its transposition. Furthermore, the paper offers a preliminary reflection on the potential directions of the Directive’s impact on national laws.